The Oracle of Tyre : the Septuagint of Isaiah XXIII as version and vision - Kooij, Arie van der, 1945- (Supplements to Vetus Testamentum,, 1998)
The volume deals with the Septuagint version of Isaiah 23, the Oracle of Tyre. The text of this chapter serves as an illustration of a comprehensive method of analysis which is described in the first part of the book. After a study of the Masoretic text the Septuagint version is dealt with from several points of view: in comparison with the Masoretic text, as text in its own right, as to its genre ('vision'), and concerning its Hebrew Vorlage. Due attention is paid to the Isaiah texts from Qumran. The last part of the book contains a chapter on the reception of LXX Isaiah 23 in patristic commentaries and also an appendix of text critical notes on Isaiah 23 according to the principles of the Biblica Hebraica Quinta .